Matrices and society - Bradley, Ian; Meek, Ronald (England Penguin books, 1986)
Matrices offer some of the most powerful techniques in modem mathematics. In the social sciences they provide fresh insights into an astonishing variety of topics. Dominance matrices can show how power struggles in offices or committees develop; Markov chains predict how fast news or gossip will spread in a village; permutation matrices illuminate kinship structures in tribal societies. All these invaluable techniques and many more are explained clearly and simply in this wide-ranging book.
Keywords: Social sciences Mathematics; Mathematics; Social science Methodology